Preparation and properties of isocyanate self-healing microcapsule cement-based material. - Yanqing Xian (PLoS ONE)
Self-healing microcapsule cement-based materials autonomously repair microcracks within the matrix. This study utilized the interfacial polymerization method to prepare isocyanate microcapsules, incorporating montmorillonite to enhance the wall material. The optimized synthesis conditions were established as follows: a reaction time of 2 hours at 50°C, using 3g of wall material, 13.5g of core material, and 1% montmorillonite, achieving a core material content of 61.5%. Both micro and macro analyses confirm the microcapsules' excellent alkaline resistance and compatibility with cement-based materials. The ideal microcapsule concentration was determined to be 4%, which increased the compressive strength recovery rate of the self-healing mortar to 117.38%.